The construct and criterion validity of the multi-source feedback process to assess physician performance: a meta-analysis - Al Ansari A (Advances in Medical Education and Practice, 2014)
Ahmed Al Ansari,1 Tyrone Donnon,2 Khalid Al Khalifa,1 Abdulla Darwish,3 Claudio Violato4 1Department of General Surgery, Bahrain Defense Force Hospital, Riffa, Kingdom of Bahrain; 2Medical Education and Research Unit, Department of Community Health Sciences, Faculty of Medicine, University of Calgary, AB, Canada; 3Department of Pathology, Bahrain Defense Force Hospital, Riffa, Kingdom of Bahrain; 4Department of Medical Education, Faculty of Medicine, University Ambrosiana, Milan, Italy Background: The purpose of this study was to conduct a meta-analysis on the construct and criterion validity of multi-source feedback (MSF) to assess physicians and surgeons in practice. Methods: In this study, we followed the guidelines for the reporting of observational studies included in a meta-analysis. In addition to PubMed and MEDLINE databases, the CINAHL, EMBASE, and PsycINFO databases were searched from January 1975 to November 2012. All articles listed in the references of the MSF studies were reviewed to ensure that all relevant publications were identified. All 35 articles were independently coded by two authors (AA, TD), and any discrepancies (eg, effect size calculations) were reviewed by the other authors (KA, AD, CV). Results: Physician/surgeon performance measures from 35 studies were identified. A random-effects model of weighted mean effect size differences (d) resulted in: construct validity coefficients for the MSF system on physician/surgeon performance across different levels in practice ranged from d=0.14 (95% confidence interval [CI] 0.40–0.69) to d=1.78 (95% CI 1.20–2.30); construct validity coefficients for the MSF on physician/surgeon performance on two different occasions ranged from d=0.23 (95% CI 0.13–0.33) to d=0.90 (95% CI 0.74–1.10); concurrent validity coefficients for the MSF based on differences in assessor group ratings ranged from d=0.50 (95% CI 0.47–0.52) to d=0.57 (95% CI 0.55–0.60); and predictive validity coefficients for the MSF on physician/surgeon performance across different standardized measures ranged from d=1.28 (95% CI 1.16–1.41) to d=1.43 (95% CI 0.87–2.00). Conclusion: The construct and criterion validity of the MSF system is supported by small to large effect size differences based on the MSF process and physician/surgeon performance across different clinical and nonclinical domain measures. Keywords: multi-source feedback system, meta-analysis, clinical performance, construct validity, criterion validity